A STRATEGY FOR TEACHING ARABIC SOUNDS TO STUDENTS OF THE LINGUISTIC PREPARATION DEPARTMENT AT AL-RAYA UNIVERSITY - Yunus Buniyaminu Gbodofu; Abdul Fatah Muhtar; Jajang Komaludin; Uril Bahruddin (UNiversitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
A STRATEGY FOR TEACHING ARABIC SOUNDS TO STUDENTS OF THE LINGUISTIC PREPARATION DEPARTMENT AT AL-RAYA UNIVERSITYThere are phonetic errors among many students of the Department of Language Preparation at Al-Raya University, especially in letters that are unparalleled in their mother tongue. The objectives of this study are to describe the strategy of teaching Arabic sounds at Al-Raya University in the Department of Language Preparation. This study relied on the qualitative descriptive approach and the case study methodology. The result of this study is that the strategy of teaching Arabic sounds at Al-Raya University in the Department of Language Preparation includes setting the goal of trying to pronounce Arabic letters correctly, and the use of educational methods is by using computers, the method of repetition, and through a dedicated application in teaching sounds on the Internet, and the use of the means available to it as a dedicated application on the Internet, and the computer, and images related to sounds and letter exits.استراتيجية تدريس الأصوات العربية لطلاب قسم الإعداد اللغوي بجامعة الراية هناك الأخطاء الصوتية لدى كثير من طلاب قسم الإعداد اللغوي بجامعة الراية، خاصة في الأحرف التي لا مثيل لها في لغتهم الأم. وأهداف هذه الدراسة هي وصف استراتيجية تدريس الأصوات العربية بجامعة الراية في قسم الإعداد اللغوي. واعتمدت هذه الدراسة على المدخل الوصفي الكيفي ومنهج دراسة الحالة. ونتيجة هذه الدراسة هي أن استراتيجية تدريس الأصوات العربية بجامعة الراية في قسم الإعداد اللغوي تشمل على وضع الهدف هو محاولة نطق الحروف العربية نطقا صحيحا، واستخدام الطرائق التعليمية هي عن طريقة استعمال أجهزة الكوبيوتر، وطريقة التكرار، وطريق تطبيق مخصص في تعليم الأصوات على الإنترنيت، واستخدام الوسائل المتاحة له كتطبيق مخصص على الإنترنيت، والكوبيوتر، والصور المتعلقة بالأصوات ومخارج الحروف.